Movimentos sociais em rede e a construção de identidades: a marcha das vadias - SM e a experiência do feminismo em redes comunicação - Tomazetti, Tainan Pauli (2015)
This study aims to investigate the construction process of collective identities in the social movement Slut Walk SM, collective action empirically located in Santa Maria, center of Rio Grande do Sul state in southern Brazil, from network communication dynamics built between the online and offline environments. We start, therefore, the conceptual approach that shapes the contemporary social movements along the processes of communication and information. Taking this premise in mind, we turn to the context of digital networks ubiquity and the Internet communication to reflect its appropriation in the effectuation and coordination of collective actions organization developed nowadays. With emphasis on communication processes, the work is performed from ethnographic experience in a communication research, in particular, from the combination of a field observations between online and offline environments. Thus, from a previous literature review, we define the cultural social movements as the Slut Walk, as analytical constructs developed around actions related to collective identities, oppositions, conflicts and struggle projects. Moreover, with the gender theory we present a brief conceptual framework about the universe of contemporary feminism and its contextual crossings on the ground of communication. Also, with the network society concept, we reflect the particularities of a social context organized through the communication and technological changes, and relate to the current configuration of the network social movements. From this, the research focuses on the interpretation of the research field reaching the settings that constitute the Slut Walk - SM as a social movement anchored by network communication logic through social uses of a Page and a Group of discussion in the social network Facebook. In the end, the study revealed that the communication network integrates the dynamics of identity construction of the Slut Walk under the scope of the differences, of gender policies, and senses about feminism. Senses, that are deliberate from the positions, opinions, debates and conflicts between the subjects in networks and on the streets.